Betting against beta no mercado acionário brasileiro - Nascimento, Felipe Merlo (2017)
In this paper, we present empirical evidence to investigate whether the propositions of the model of Frazzini and Pedersen (2014) apply to the Brazilian stock market. Using data from the year 2000 up to the first quarter of 2017, we find that the SML of this Market had a lower slope than that predicted by CAPM. In fact, it turned out to be negative, and this result was observed both in the time-series and in the cross-sectional analyzes. As a methodology to raise this evidence, 10 portfolios were created, organized in ascending order according to their respective betas. We calculated the returns relative to each portfolio and, with them, it was possible to verify that the portfolios with the highest beta performed less excess returns. In addition, we found that the Sharpe ratio was higher the lower the beta of the portfolios. Another proposition verified empirically in the Brazilian stock market, and in the considered period, was that the return of the BAB portfolios was positive. In addition, it was the largest one compared to others portfolios, and had the highest expected excess of return per unit of risk. Regarding the alpha, it was expected that the portfolios with higher beta had lower alpha. It was possible to verify this trend, but not in an undeniable way. This motivated us to make a small change in the model of Frazzini and Pedersen, which created a relation between the return of each one of the portfolios and the one of the BAB portfolio. The mathematical prediction, derived from the modified model, says that the coefficient of this relation is smaller the bigger the beta. It was possible to raise this empirical evidence in a clear way. This point was the great differential of this work, since we were the first to raise such evidence and to show that the BAB portfolios can be used as explanatory variable.